Investigating the performance of P3HT:PCBM organic solar cells involving gamma-irradiated PEDOT:PSS layer - Yagci, Ozlem; Yesilkaya, Serco Serkis; Okutan, Murat; Icelli, Orhan (TAYLOR & FRANCIS LTD, 2017)
In this work, we investigated for the first time the characteristics of (poly (3-hexylthiopene) and [6, 6]-phenyl C61-butyric acid methyl ester) (P3HT:PCBM) blends-based organic solar cell with 1.25mg/mL boric-acid (H3BO3)-doped poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) layer which is irradiated under the 40 Gray (Gy) dose of gamma () ray. Experimental results showed that the parameters of solar cell improved with exposure to low-dose gamma radiation. In particular, it has provided a significant improvement in short-circuit current density (J(sc)) and power conversion efficiency (PCE). About 49% increase in PCE to 1.22% and 40% increase in J(sc) to 6.28mA/cm(2) was obtained between the bare device and the device containing irradiated PEDOT:PSS:H3BO3. Also, it was determined that the H3BO3-doped PEDOT:PSS is more stable to temperature. More importantly, solar cell containing gamma-irradiated PEDOT:PSS:H3BO3 showed best performance comparing to conventional PEDOT:PSS-based cell.
Keywords: PEDOT:PSS; P3HT:PCBM; organic materials; boric acid; organic solar cells; gamma-ray irradiation; UNCERTAINTY EVALUATION; ELECTRICAL-PROPERTIES; THIN-FILMS; RADIATION; DEGRADATION; STABILITY; Nuclear Science & Technology; Physics